2003
DOI: 10.1007/s00442-002-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formica ants on soil fauna-results from a short-term exclusion and a long-term natural experiment

Abstract: Wood ants (Formica spp.) were hypothesised to affect the composition and greatly reduce the abundance of large-sized soil fauna by predation. This was tested in two ways. Firstly, a 4-year-long experimental study was carried out in a mixed forest. Five ant-free 1.3-m(2) plots were created by fenced exclosures within an ant territory. Five nearby plots had fences with entrances for the ants. In addition, five non-fenced control plots were selected. Soil fauna (e.g. Coleoptera, Diptera larvae, Collembola and Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…However, to date most studies have not provided any evidence of interactions between spiders and ants aVecting population densities (Otto 1965;van der Aart and de Wit 1971;Brüning 1991;Lenoir et al 2003;Gibb 2003). Our results provide experimental evidence for negative interactions between ants and spiders in a grassland (Fig.…”
Section: Intraguild Interactionssupporting
confidence: 72%
See 2 more Smart Citations
“…However, to date most studies have not provided any evidence of interactions between spiders and ants aVecting population densities (Otto 1965;van der Aart and de Wit 1971;Brüning 1991;Lenoir et al 2003;Gibb 2003). Our results provide experimental evidence for negative interactions between ants and spiders in a grassland (Fig.…”
Section: Intraguild Interactionssupporting
confidence: 72%
“…However, the authors concluded that not direct predation but the disturbance of spiders by ants was important. In contrast, such eVects could not be demonstrated in other studies (Otto 1965;van der Aart and de Wit 1971;Brüning 1991;Gibb 2003;Lenoir et al 2003). Brüning (1991) tested the eVects of Formica polyctena on spiders in a forest ecosystem without Wnding any diVerence in the density or composition of the spider community neither inside nor outside the hunting area of ants.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, this study did not provide evidence for a negative effect of RWA on the epigeic invertebrate community. This is surprising in the light of former investigations indicating a strong effect of RWA on epigeic invertebrates (Kajak et al, 1972;Niemelä et al, 1992;Laakso, 1999;Hawes et al, 2002;Reznikova & Dorosheva, 2004;Dorosheva & Reznikova, 2006; but see also Lenoir et al, 2003). It is possible that specific abiotic factors of clear-cut areas (e.g.…”
Section: Discussioncontrasting
confidence: 39%
“…Ants prey upon soil-and litter-dwelling invertebrates, and, at least in come cases, affect the abundance of particular soil taxa and the composition of soil communities (Wagner et al 1997, Laakso 1999, Laakso and Setala 2000, Lenoir et al 2003, Wilson 2005, MoyaLorano and Wise 2007, Wardle et al 2011, Sanders and Frank van Veen 2011. Ants may indirectly influence soil nutrients by suppressing populations of microbe-feeding mites and Collembolans.…”
Section: Introductionmentioning
confidence: 99%